(untitled) (Medico Legal Update, 2019)
Existing X-ray medical imaging acquired the image data of X-ray absorption difference using the difference in density of the subject tissue. X-ray scattering and phase contrast imaging technology is a technology that dramatically increases boundary information between homogeneous materials of similar density using scattering and phase contrast information. To acquire and evaluate absorption, scattering, and phase contrast images, using the phantom made of polyethylene, on a round rod with a diameter of 3?1cm, a hole with a diameter of 0.5cm was drilled on 5 round rods, and the medical phantom was produced by sealing with sodium chloride, neon, calcium, phosphorus, and selenium powder. At a distance of 40cm from the focus, the distribution of absorbed doses have shown 1,277 ± 0.31?Gy in the center area. The measurement dose in the anode side direction was 110.1 ± 0.35?Gy and the cathode side direction was 117.7 ± 0.77?Gy. It has shown dose inequality that depends on the geometry of the target. It has shown similar tendency in 60cm and 80cm Compared with absorption images in graphite materials, it was confirmed that scattering and phase contrast images were showing relatively high image information. These results are expected to be utilized as an important basic data for reducing medical exposure dose and acquiring, evaluating and utilizing X-ray absorption, scattering and phase contrast images.